ONLAY VERSUS SUBLAY TECHNIQUES FOR INCISIONAL HERNIA REPAIR: 30-DAY POSTOPERATIVE OUTCOMES - Eduardo Ferreira Martins; Marcos Dal Vesco Neto; Pedro Klanovichs Martins; Lucas Dos Santos Difante; Lara Luz de Miranda Silva; Henrique Rasia Bosi; Bernardo Silveira Volkweis; Leandro Totti Cavazzola (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2022)
ABSTRACT BACKGROUND: The development of an incisional hernia is a common complication following laparotomy. It also has an important economic impact on healthcare systems and social security budget. The mesh reinforcement of the abdominal wall was an important advancement to increase the success of the repairs and reduce its long-term recurrence. The two most common locations for mesh placement in ventral hernia repairs include the premuscular (onlay technique) and retromuscular planes (sublay technique). However, until now, there is no consensus in the literature about the ideal location of the mesh. AIM: The aim of this study was to compare the two most common incisional hernia repair techniques (onlay and sublay) with regard to the complication rate within the first 30 days of postoperative care. METHOD: This study analyzes 115 patients who underwent either onlay or sublay incisional hernia repairs and evaluates the 30-day postoperative surgical site occurrences and hernia recurrence for each technique. RESULTS: We found no difference in the results between the groups, except in seroma formation, which was higher in patients submitted to the sublay technique, probably due to the lower rate of drain placement in this group. CONCLUSION: Both techniques of mesh placement seem to be adequate in the repair of incisional hernias, with no major difference in surgical site occurrences.